The Effect of Counseling on Knowledge and Compliance of Patient with Diabetes Mellitus at Wates Public Health Center of Pringsewu - Pratiwi, Mida; Febriani, Wiwi; Wati, Desti Ambar (Universitas Aisyah Pringsewu, 2022)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by increased glucose levels in the blood. Doing counseling is one way to increase knowledge, patient compliance, and achieve optimal health. Lack of knowledge and patient non-compliance with treatment resulted in problems in improving the condition of patients with diabetes mellitus. The objective of this study was to determine the effect of counseling on the knowledge and compliance of patients with diabetes mellitus. This study was an observational study by using a quasi-experimental method with pre and post-control groups to see the level of patient knowledge and assess the effectiveness of therapy as seen by the decrease in blood sugar levels of patients with diabetes mellitus at the Wates Public Health Center of Pringsewu from January to March 2021 with a study sample of 54 patients. The results showed that counseling can increase knowledge and compliance in diabetic patients with a p-value less than 0.05, which means that there is a significant difference. This research was given counseling by pharmacists and nutritionists to increase knowledge and compliance of patients with diabetes mellitus and improve blood glucose control in diabetic patients at Wates Public Health Center of Pringsewu. Abstrack: Diabetes mellitus (DM) merupakan penyakit metabolik kronis yang ditandai dengan peningkatan kadar glukosa dalam darah. Konseling merupakan salah satu cara untuk meningkatkan pengetahuan, kepatuhan pasien dan mewujudkan kesehatan yang optimal. Pengetahuan yang kurang dan ketidakpatuhan pasien terhadap pengobatan mengakibatkan permasalahan dalam perbaikan kondisi pasien diabetes melitus. Tujuan penelitian ini adalah untuk mengetahui pengaruh konseling terhadap pengetahuan dan kepatuhan pasien diabetes mellitus. Penelitian ini bersifat observasional dengan menggunakan metode quasi eksperimental dengan pre dan post control group untuk melihat tingkat pengetahuan pasien dan menilai efektivitas terapi yang dilihat dari penurunan kadar gula darah pasien diabetes mellitus di Puskesmas Wates Pringsewu pada bulan Januari-Maret 2021 dengan sampel penelitian sebanyak 54 pasien. Hasil penelitian menunjukan bahwa pemberian konseling dapat meningkatkan pengetahuan dan kepatuhan pada pasien diabetes dengan p value kurang dari 0.05 yang artinya terdapat perbedaan bermakna. Penelitian ini adalah pemberian konseling yang dilakukan oleh farmasis dan ahli gizi dapat meningkatkan pengetahuan dan kepatuhan pasien diabetes melitus dan meningkatkan terkontrolnya glukosa darah sewaktu pada pasien diabetes di Puskesmas Wates Pringsewu.